Evaluation of the microwave-assisted enzymatic inactivation process of tomato pulp - FONSECA, Ingrid Johana Mesa; GUILHERME, Ederson; SILVEIRA JUNIOR, Vivaldo (Food Science and Technology, 2023)
In this study, the thermal and non-thermal effects of microwaves on the enzymatic inactivation of pectin methylesterase in the tomato pulp were validated. An amount of 30 kg of tomato pulp was subject to two different types of treatments: thermal effects and then non-thermal effects using microwaves, implementing a system that allowed simultaneous cooling of microwave heating. An experimental rotational central composite design was used to analyze the effect of the interactions of the variables involved in the process. The activity analysis of the PME enzyme, pH, titratable acidity, total soluble solid, and color was performed on both processed and non-processed tomato pulps, which showed that the heating process with thermal effect did not significantly change physical-chemical properties and were found to be more effective, reaching the enzymatic inactivation of 99% and the temperature of 80ºC after 425 s of processing. However, the non-thermal analysis with temperatures at a maximum of 40ºC attained 56.8% of enzymatic inactivation.